Protein tyrosine phosphatases - Dixon, Jack (Henry Stewart Talks, 2010)
Kinases and phosphatases, Ways to remove phosphate from proteins, Class I Cys-based PTPs, Phosphatase families, Mutational analysis of PTP-1, Sequences at active site, Phospho-enzyme intermediate, pH stability of phosphoprotein phosphate, Site-directed mutational analysis of VHR, How PTPs share a catalytic active site motif, Sequences of phosphatases, The bacterial Yop 2b phosphatase activity, Bacterial growth in the spleen of mice, Yop 2b in eukaryotic macrophages, Interaction between Yersinia and a target cell, Phosphatases as tumor suppressor genes, PTEN and myotubularin structure, PTEN-10q23.3, Frequency of PTEN mutations, Kinetic constants of dual-specificity phosphates, How PTEN is a "lipid" phosphatase, How PTEN might inhibit cell survival, Effect of PTEN overexpression on PIP3 production, Effect of PTEN expression on PI 3-kinase activation, Inositol phosphatase activity of PTEN, PTEN tumor suppressor activity, Key PTEN and PIP3 researchers -RNA interference in C.elegans, RNA interference protocol for fly S2 cells, Mammalian, C.elegans and fly signaling cascade, How PTEN inhibits Akt activity, The active site pocket of PTEN, Sequence alignment of PTEN catalytic site